Effectiveness of printed infographics to promote breastfeeding in the Sonora population - Adriana V. Bolaños-Villar; Irene L. Beltrán-Sauceda; Ana M. Calderón- (Permanyer, 2023)
Background: In Mexico, the prevalence of exclusive breastfeeding for 6 months is low (28.6%); in the state of Sonora, it is only 15%. Effective strategies are needed to promote it. The aim of this study was to evaluate the effectiveness of printed infographics designed to promote breastfeeding in mothers from Sonora. Methods: We prospectively studied lactation regimes from birth. Intention to breastfeed, general characteristics of the mother-infant dyad, and telephone number were registered. Participants received educational training in the hospital; those assigned to the intervention group (IG) also received up to five infographic materials (designed and evaluated previously) in different perinatal periods, while those in the control group (CG) did not. At two months postpartum, the infant feeding practice and reasons for introducing formula were collected by phone. Data were analyzed with the χ2 test. Results: Of 1705 women enrolled, 57% were missed during follow-up. Although 99% of participants planned to breastfeed, 92% of IG did so, compared to 78% of CG (95% Confidence interval [CI]: 7.04, 19.98; p < 0.0001). Mothers in the IG used more formula than those in the CG (6 vs. 21%; 95% CI: −20.54, −8.0; p < 0.0001), arguing insufficient milk production. The delivery of three infographics (one in prepartum and two in the hospital- training), or five infographics in different periods, promoted breastfeeding in 95% of participants. Conclusions: The distribution of printed infographics and initial training promoted breastfeeding, although not its exclusivity.